ISLAMIC LEGAL PERSPECTIVE ON PROTECTION OF WOMEN VICTIMS OF FEMICIDE IN INDONESIA - Nuranisa Nuranisa; Nur Wahyuni; Kurniati Kurniati (ANAYASA : Journal of Legal Studies, 2026)
The phenomenon of femicide, or the killing of women based on gender-related motives, in Indonesia has shown a troubling increase, while the national legal system has yet to establish specific regulations addressing this crime. This legal vacuum results in the handling of femicide cases being limited to general homicide provisions under the Criminal Code (KUHP), without adequately considering the gender-based dimensions inherent in such acts.This study aims to analyze the protection of women as victims of femicide from the perspectives of Islamic law and positive law, as well as to examine how the principles of maqāṣid al-syarī‘ah and siyāsah syar‘iyyah can serve as a philosophical foundation for formulating national legal policies capable of preventing femicide and protecting women.The research employs a normative juridical approach with comparative and conceptual analysis, utilizing primary sources such as the Qur’an, Hadith, and principles of Islamic law, alongside secondary sources including the Criminal Code (KUHP), the Law on Sexual Violence Crimes (UU TPKS), and relevant legal literature.The findings indicate that Islamic law firmly prohibits all forms of violence and the killing of women, as such acts fundamentally contradict the principles of ḥifẓ al-nafs (protection of life) and the overarching notion of justice within Islamic jurisprudence. Meanwhile, the national legal system urgently requires regulatory reform through the integration of the values of maqāṣid al-syarī‘ah and siyāsah syar‘iyyah into the formation of a Gender-Just, Humanistic, and Comprehensive Anti-Femicide Law.